Genome-Wide Association Study Meta-Analysis of Long-Term Average Blood Pressure in East Asians. (April 2017) - Li, Changwei; Kim, Yun Kyoung; Dorajoo, Rajkumar; Li, Huaixing; Lee, I-Te; Cheng, Ching-Yu; He, Meian; Sheu, Wayne H-h; Guo, Xiuqing; Ganesh, Santhi K.; He, Jiang; Lee, Juyoung; et al.
Abstract : Background—: Genome-wide single marker and gene-based meta-analyses of long-term average (LTA) blood pressure (BP) phenotypes may reveal novel findings for BP. Methods and Results—: We conducted genome-wide analysis among 18 422 East Asian participants (stage 1) followed by replication study of ⩽46 629 participants of European ancestry (stage 2). Significant single-nucleotide polymorphisms and genes were determined by a P <5.0×10 −8 and 2.5×10 − 6, respectively, in joint analyses of stage-1 and stage-2 data. We identified 1 novel ARL3 variant, rs4919669 at 10q24.32, influencing LTA systolic BP (stage-1 P =5.03×10 − 8, stage-2 P =8.64×10 − 3, joint P =2.63×10 − 8 ) and mean arterial pressure (stage-1 P =3.59×10 − 9, stage-2 P =2.35×10 − 2, joint P =2.64×10 − 8 ). Three previously reported BP loci ( WBP1L, NT5C2, and ATP2B1 ) were also identified for all BP phenotypes. Gene-based analysis provided the first robust evidence for association of KCNJ11 with LTA systolic BP (stage-1 P =8.55×10 − 6, stage-2 P =1.62×10 − 5, joint P =3.28×10 − 9 ) and mean arterial pressure (stage-1 P =9.19×10 − 7, stage-2 P =9.69×10 − 5, joint P =2.15×10 − 9 ) phenotypes. Fourteen genes ( TMEM180, ACTR1A, SUFU, ARL3, SFXN2, WBP1L, CYP17A1, C10orf32, C10orf32 - ASMT, AS3MT, CNNM2, and NT5C2 at 10q24.32; ATP2B1 at 12q21.33; and NCR3LG1 at 11p15.1) implicated by previous genome-wide association study meta-analyses were also identified. Among the loci identified by the previous genome-wide association study meta-analysis of LTA BP, we transethnically replicated associations of the KCNK3 marker rs1275988 at 2p23.3 with LTA systolic BP and mean arterial pressure phenotypes ( P =1.27×10 − 4 and 3.30×10 − 4, respectively). Conclusions—: We identified 1 novel variant and 1 novel gene and present the first direct evidence of relevance of the KCNK3 locus for LTA BP among East Asians. Abstract : Supplemental Digital Content is available in the text.